East Asian Financial Contagion under DCC-Garch - Cho, J. H.; Parhizgari, A. M. (Universiti Utara Malaysia, 2009)
We consider the definition and measurement of contagion by analysing the 1997 East Asian financial crisis in the equity markets of eight countries using dynamic conditional correlation (DCC). Taking Thailand and Hong Kong as alternative sources of contagion, a total of fourteen source-target pairs is analyzed. We define contagion as the statistical break in the computed DCCs as measured by the shifts in their means and medians. In the DCC process, the parameters of each pair of source-target country contagion are allowed to vary and be dictated by the data. Contagion is tested using DCC means and medians difference tests. Our findings indicate the presence of contagion in the equity markets across all the fourteen pairs of source-target countries that are considered.